12m-9=4m+5

Simple and best practice solution for 12m-9=4m+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12m-9=4m+5 equation:


Simplifying
12m + -9 = 4m + 5

Reorder the terms:
-9 + 12m = 4m + 5

Reorder the terms:
-9 + 12m = 5 + 4m

Solving
-9 + 12m = 5 + 4m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-4m' to each side of the equation.
-9 + 12m + -4m = 5 + 4m + -4m

Combine like terms: 12m + -4m = 8m
-9 + 8m = 5 + 4m + -4m

Combine like terms: 4m + -4m = 0
-9 + 8m = 5 + 0
-9 + 8m = 5

Add '9' to each side of the equation.
-9 + 9 + 8m = 5 + 9

Combine like terms: -9 + 9 = 0
0 + 8m = 5 + 9
8m = 5 + 9

Combine like terms: 5 + 9 = 14
8m = 14

Divide each side by '8'.
m = 1.75

Simplifying
m = 1.75

See similar equations:

| 8x+8+7x-4= | | 3(y+4)=4(y-2) | | 1x+-3=-10 | | 150m-125m+33600=35000-150 | | 2.50(x+15.00)=662.50 | | 5(s+3)=45 | | x=2+-0.5X | | 6(2+c)=5(c-8) | | 12+3m= | | u^2+10+21=0 | | 2.50(x+15.00)=412.50 | | 2(x+1)=6-X | | 25=p/6+(-19) | | -x^2+7x+30=0 | | 4(10b+7)-6b= | | 4(2c+3)-2=2(4c+6) | | 5d-15= | | 33-8x=13+12x | | 2x-2=2(x+5) | | 5.7x-17.3+5.3x=6.4+12x | | 3x=9(x-5) | | 10a+2a= | | f(-4)=3x^2-6x+5 | | 36-11x=20+5x | | 3(x+2)=6x-1 | | 36-11x=205x | | 4-15x-25x^2=0 | | y-4(3y-6)+8=y | | 6m+30=10m | | 6s-11=-25+5 | | 30t+1=t | | q-3+4q=12 |

Equations solver categories